2021
DOI: 10.1038/s41533-021-00252-w
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of mental health care for people with COPD: a qualitative study of clinicians’ perspectives

Abstract: Anxiety and depression are common mental health illnesses in people with chronic obstructive pulmonary disease (COPD). However, patients often decline formal mental health care with barriers identified at the patient, health provider and health system levels. Currently clinicians’ perspectives on this issue are not well understood. A qualitative study using semi-structured interviews was undertaken to explore clinician perceived barriers and facilitators to acceptance of psychological care amongst people with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Unforeseen and chronic events in COPD can lead to the anxiety that provokes somatic and emotional symptoms of anxiety or panic. Such patients are more likely to seek medical help, more likely to go for routine and unscheduled check-ups, more likely to be prescribed anti-inflammatory therapy, and have more hospital treatments as well as longer duration [ 30 ]. The higher the level of anxiety, the worse the control of the disease, and the worse the quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unforeseen and chronic events in COPD can lead to the anxiety that provokes somatic and emotional symptoms of anxiety or panic. Such patients are more likely to seek medical help, more likely to go for routine and unscheduled check-ups, more likely to be prescribed anti-inflammatory therapy, and have more hospital treatments as well as longer duration [ 30 ]. The higher the level of anxiety, the worse the control of the disease, and the worse the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the level of anxiety, the worse the control of the disease, and the worse the quality of life. According to the literature, the prevalence of panic attack is nearly ten times higher in people with COPD than in the general population [ 30 ]. Mental health problems with COPD are associated with a reduced ability to cope with the disease itself, which is progressive, declining lung function and more pronounced dyspnea, poorer quality of life, more frequent exacerbations and hospitalizations, poor adherence to treatment [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies reported that in less than 44% of people with COPD, clinically relevant increased levels of depression and/or anxiety were adequately diagnosed and that only 31% of them had received any treatment for these comorbid psychological conditions [ 187 ]. These data have been subsequently confirmed [ 7 ], stressing that less than one-third of people with COPD and mental health problems receive adequate management, despite the recommendations of the Global Initiative for Chronic Obstructive Lung Disease guidelines to actively screen for and manage psychological comorbidities [ 188 ]. Hence, some important clinical and research-related challenges should be addressed in the future to optimise the management of psychological distress in COPD, which will be discussed below ( figure 2 ).…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…While several types of nonpharmacological interventions have been empirically validated, the availability of such interventions is limited in clinical practice, which is reported as a barrier to initiating discussions of mental health by respiratory clinicians [ 188 ]. An international survey among members of respiratory societies indicates that mental health specialists, e.g.…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…Various studies suggest that routine screening for depression and anxiety in COPD patients and an integrated treatment approach may improve the treatment outcomes. Unfortunately, anxiety symptoms may go undetected in routine clinical practice due to factors such as physician-perceived barriers, system-related barriers [8,9], and difficulty in differentiating these anxiety symptoms from somatic symptoms of COPD like breathlessness. Therefore more than 50% of COPD patients with comorbid anxiety are not getting any appropriate treatment [8].…”
Section: Introductionmentioning
confidence: 99%